A mixed-methods analysis of best practices for land-grant university mobile applications from a user experience design perspective - Valoris, Michelle, author; Hallahan, Kirk, advisor; Kim, Jangyul, committee member; McKelfresh, David, committee member (Colorado State University. Libraries, 2015)
A content analysis of 30 mobile applications for the largest land-grant universities in the United States was conducted to examine the use of recognized best practices for mobile application development. A total of 49 variables were identified as best practices across five hierarchical categories of user experience (UX) design based on a model proposed by Garrett (2011). These included: visual design, user interface and navigation design, interaction design and information architecture, content and services offered, and functional and technical specifications. Based on quantitative scores for each of the variables, the best overall apps were identified and reviewed using qualitative description analysis. The best overall app was created by the University of New Hampshire; other top apps examined in the study were developed by the University of Arizona, Ohio State University, University of Florida, Washington State University and Michigan State University. The findings revealed that it was very difficult for a mobile app to be exemplary in all five of the UX categories and thus comply with best practices. Analysis of the top six ranked applications portrayed how the UX categories and best practices interacted with and relied on one another to create a successful user experience. The study provided guidelines for universities to build more effective mobile apps and a foundation for further research into mobile application best practice measures, mobile app strategies, and the user experience of mobile applications.